Causes and Management of Industrial Disputes between University Management and the Junior Staff at the University of Cape Coast, Ghana - Nyan, Evelyn (Ghana Journal of Higher Education Management, 2024)
The study examined the causes and management of industrial disputes between University management and the junior staff represented by the Teachers and Educational Workers Union (TEWU) at the University of Cape Coast. The study which was descriptive employed 337 respondents. Two sets of questionnaire were used to gather data for the study. The study showed that issues concerning wages and salaries are the leading factors that account for disputes between the union and management in the University of Cape Coast. However, according to the study, such issues are mostly resolved amicably through negotiation without external intervention. The study further revealed that majority of the junior staff did not have knowledge about the conditions of service which is supposed to be their reference material when they want issues to be addressed. Based on the findings from the study, it is recommended that issues concerning salaries and wages and other economic benefits to staff be addressed by management promptly to prevent the occurrence of industrial unrest. Management and the TEWU executives shouldperiodically update the junior staff on policies, rules, regulations and the conditions of service.